2006
DOI: 10.1300/j047v18n01_09
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes Toward Biotech Foods in China

Abstract: Based on a large-scale survey in 11 cities, this study employs probit and logit models to estimate the effects of various explanatory variables on the likelihood of biotech food acceptance in China. Analyses focus on biotech soybean oil, input-and output-trait biotech rice, and livestock products fed with biotech corn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 8 publications
7
22
0
Order By: Relevance
“…In line with the study about FBR acceptance (see section 1.3.1.1), WTP for a GM product is expected to be influenced by GM food knowledge, consumer perceptions, and socio-demographic indicators (Bredahl et al, 1998;Verdurme et al, 2003b;House et al, 2004;Ajzen, 2005;Han and Harrison, 2006;Lin et al, 2006;Costa-Font et al, 2008;De Groote and Kimenju, 2008), although research regarding the effect of the latter is inconclusive (Lusk et al, 2001a;Umberger and Feuz, 2004). The importance of these determinants are investigated for the stated WTP, which is based on the survey that is used to explain FBR acceptance (see section 3.2.2).…”
Section: Determinants Of Wtpmentioning
confidence: 74%
See 2 more Smart Citations
“…In line with the study about FBR acceptance (see section 1.3.1.1), WTP for a GM product is expected to be influenced by GM food knowledge, consumer perceptions, and socio-demographic indicators (Bredahl et al, 1998;Verdurme et al, 2003b;House et al, 2004;Ajzen, 2005;Han and Harrison, 2006;Lin et al, 2006;Costa-Font et al, 2008;De Groote and Kimenju, 2008), although research regarding the effect of the latter is inconclusive (Lusk et al, 2001a;Umberger and Feuz, 2004). The importance of these determinants are investigated for the stated WTP, which is based on the survey that is used to explain FBR acceptance (see section 3.2.2).…”
Section: Determinants Of Wtpmentioning
confidence: 74%
“…This thesis one of the first to conduct consumer research about a 'consumer-friendly' GM food crop in a high-risk region where the need of exploiting its benefits is the highest. When reviewing Chinese consumer studies on GM food, whether the objective is to analyze acceptance (Lin et al, 2004;Ho et al, 2006;Huang et al, 2006b), conduct a segmentation study Zhang et al, 2010) or to investigate the WTP for GM food and rice Liu, 2009), or when experimental auctions are applied (Kachelmeier and Shehata, 1992;Wang and McCluskey, 2010), the focus is solely on urban China, which further supports the selected research location.…”
Section: Empirical Contributionmentioning
confidence: 86%
See 1 more Smart Citation
“…Over the last decade several studies have investigated consumer's attitude toward biotech foods in China such as, Li et al 2002;Zhong et al 2003;Hu and Chen, 2004;Ho and Vermeer, 2004;Curtis et al, 2006;and Lin et al, 2006. The majority of these studies found Chinese consumers are generally favorable or neutral about the use of biotechnology in crop production, feed for raising livestock and poultry, and ingredients in processed food production.…”
Section: Consumers' Attitude Toward Gm Food In Chinamentioning
confidence: 99%
“…However, the study has several limitations since it used hypothetical GM rice (GM rice has not been commercialized in China) and did not provide sufficient information to the consumers as to the difference between product enhanced GM (rice) and processed enhanced GM (soybean oil). Lin et al (2006) surveyed 1,100 consumers in 11 large-to-small cities including Beijing and Shanghai and found 46-67 percent of the consumers supported biotech food. The survey also found that the consumers are willing to pay 23-52 percent premium for non-GM soybean oil and 41-74 percent for non biotech rice.…”
Section: Consumers' Attitude Toward Gm Food In Chinamentioning
confidence: 99%